New Pests of Tropical Pines in India - Gupta, B. K. (Indian Forester, 1980)
Gregarious flowering of BambUsa nutans in 1980 is reported from Dehra Dun. Readers are requested to keep a watch in other areas of its occurrence, Apart from the irregular sporadic flowering, this bamboo seems to flower gregariously after every 35 year. There are at least 2 separate flowering cycles involved, each of the same duration, the last having manifested in 1966.